Spectrophotometric Determination of Ni+2 by 3- ((2- Hydroxyphenyl) imino) indolin- 2- one - Al- Mofti, Braa Waled; Al- Azrak, Abdulkder (Journal of natural sciences, life and applied sciences, 2021)
3- ((2- Hydroxyphenyl) imino) indolin- 2- one was prepared by reacting isatin with 2- aminophenol(HIAP),The reagent was characterized by IR, H 1NMR spectrum, This reagent with a nickel complex forms a violet color (1: 2) at pH = 9.0, λmax =575nm and room temperature using sodium tetraborate buffer solution, The molar absorptivity 1.43 10+4 L mol- 1 cm- 1 and Sandell’s sensitivity value is 0.03800 μg cm- 2 and The Beer’s law is obeyed in the range 0.50- 5.28 μg mL- 1 of nickel (II) and the Calibration curve equation y = 0.0663x + 0.0749, R² = 0.9988.
Keywords: nickel (II); 3-(2-hydroxyphenyl)imino)indoline-2n; Spectrophotometric Determination; Ni 2; 3- ((2- hydroxyphenyl) imino) indolin- 2- one